The Palgrave Handbook of Utopian and Dystopian Literatures
XIV, 742 p. 1 illus.
Keywords: The Palgrave Handbook of Utopian and Dystopian Literatures celebrates a literary genre already over 500 years old. Specially commissioned essays from established and emerging international scholars reflect the vibrancy of utopian vision, and its resiliency as idea, genre, and critical mode. Covering politics, environment, geography, body and mind, and social organization, the volume surveys current research and maps new areas of study. The chapters include investigations of anarchism, biopolitics, and postcolonialism and study film, art, and literature. Each essay considers central questions and key primary works, evaluates the most recent research, and outlines contemporary debates. Literatures of Africa, Australia, China, Latin America, and the Middle East are discussed in this global, cross-disciplinary, and comprehensive volume.